Antibacterial and cytotoxicity of chitosan nanocomposite loaded with thymol against some cariogenic bacteria - Matin Kordestani; Marzieh Rashidipour; Hossein Mahmoudvand; Shoukofeh Jalali; Fahimeh Kooshki (Shahrekord University of Medical Sciences, 2023)
Introduction: Tooth decay as the most common infectious-nutritional disease in the world. The current work aims to investigate the antibacterial effect of thymol-loaded chitosan nanocomposite (TLCN) against Streptococcus mutans and Actinomyces viscosus as the main cariogenic bacteria. Methods: Antibacterial activity of TLCN was assessed on S. mutans and A. viscosus. The effects on protein leakage in the tested bacteria, as well as its cytotoxicity, were studied by Bradford's method and cell viability assay, respectively. Results: The size of the nanocomposite varied from 100 to 600 nm. The best minimum inhibitory concentration (MIC) related to nanocomposite + chlorhexidine was reported 2.66 for both bacteria. TLCN dose-dependently increased the protein leakage (P < 0.05). The 50% cytotoxic concentration (CC50) of nanocomposite against on normal (HGF1-PI1) and cancer (KB) cells were 149.6 and 68.4 μg/mL, respectively. Conclusion: TLCN, especially in combination with chlorhexidine, displayed potent antibacterial effects against the main cariogenic bacterial causes. Nevertheless, other examinations are required to illuminate the precise mechanisms and its toxicity mainly in clinical settings.